Fast Adaptive Thermal Buffering by a Passive Open Shell Based on Transformation Thermodynamics. Issue 7 (16th May 2018) - Liu, Yichao; Sun, Fei; He, Sailing
Abstract: By using transformation thermodynamics, an open, adaptive thermal buffer shell (TBS) is designed and experimentally implemented with natural materials (layered copper and expanded polystyrene [EPS]). The TBS can store excessive heat flux quickly in the shell and release it slowly when it is needed, which also has some distinctive features: first it is a buffer shell that can avoid external extremes in temperature (either high or low) and also provide a relatively stable temperature for the interior of the shell when the temperature outside the shell has some fluctuations; second the TBS is not thermally insulated (with holes connected to the outside world) and the buffering effect of the TBS originates from the heat recycling mechanics, not thermal insulation; third the TBS has a short response time and the temperature inside the shell can be quickly adjusted according to the average temperature outside the shell; fourth the TBS is a passive device. Unlike traditional air conditioning, the TBS can work without an external power supply. The TBS will have many applications in energy recycling systems, smart heat controlling systems, and passive heat self‐adaptation systems. Numerical simulations and experimental demonstrations are given to verify the function of the TBS. Abstract : The thermal buffer shell can store heat and neutralize external heat fluctuations due to the delay effect of thermal diffusion in the perpendicular direction and the acceleration effect of thermal diffusion in the lateral direction, which makes the temperature inside the device independent of the external environment. In contrast, heat flux will spread into the normal low thermal conductivity shell through the hole.